The Role of Morality and Self-Control in Conditioning the Criminogenic Effect of Provocation. A Partial Test of Situational Action Theory. Issue 10 (3rd October 2021) - Barton-Crosby, Jennifer; Hirtenlehner, Helmut
ABSTRACT: The role of motivation has been widely neglected in criminological research. One general framework that sheds light on the processes governing whether crime is perceived and chosen as a response to a given motivation is Situational Action Theory (SAT). The theory posits that experiences of temptation and provocation lead to criminal activity especially in the presence of weak personal moral rules and poor ability to exercise self-control. Based on a longitudinal crime survey conducted among adolescents in Austria, the current study examines whether an individual's moral rules and his or her level of self-control condition the effect of provocation on criminal involvement. Results show that various measures of provocation increase offending and that provocation is more likely to translate into criminal behavior when individuals hold weak law-consistent moral rules. Further, the capacity for self-control affects the choice of a response to provocation particularly among adolescents with weak law-consistent morality – the underlying assumption being that weak moral rules facilitate the perception of crime as a viable action alternative. Such a three-way interaction is compatible with SAT's reflections on the functioning of the moral filter and the conditional relevance of controls.